Frequency of Polycystic Ovarian Syndrome In Women Presenting with Acne Vulgaris – A Cross-Sectional Study - Malik, Asma; Shahid, Muhammad Farhan; Ahmad, Muhammad Khurram; Ayesha Anwar; Aimen Sohrab; Iqbal, Muhammad Tayyab (Pakistan Armed Forces Medical Journal, 2026)
Objective: To study the frequency of polycystic ovarian syndrome (PCOS) in women presenting with acne vulgaris in Dermatology outpatient department (OPD). Study Design: Analytical cross-sectional study. Place and Duration of Study: Department of Dermatology, Pak Emirates Military Hospital (PEMH), Rawalpindi, Pakistan, from May to Oct 2024. Methodology: The study enrolled 104 women presenting to Dermatology OPD with face acne. Patients diagnosed with acne vulgaris by a dermatologist were advised blood tests for Luteinizing Hormone (LH)/ Follicle-stimulating hormone (FSH) ratio and pelvic ultrasound for ovarian cysts. Rotterdam Criteria were used to diagnose PCOS. The frequency of PCOS in acne vulgaris patients was assessed, along with the association of acne severity with PCOS and menstrual irregularities, and the relationship between Body Mass Index (BMI) and PCOS. Chi-square analysis was used to determine association between acne vulgaris and PCOS. Results: The median age of enrolled patients was 33.50(14.00) years, and median BMI was 25.00(4.00) kg/m2. All patients had acne vulgaris, which was graded using Global Acne Grading System (GAGS) where 34(32.70%) patients had mild acne, 30(28.80%) moderate, 21(20.20%) had moderately severe acne while severe acne was seen in 19(18.30%) patients. From the study population, PCOS was diagnosed using the Rotterdam Criteria in 42(40.40%) acne vulgaris patients and 62(59.60%) acne patients did not have underlying PCOS. Menstrual abnormalities were the most common clinical feature observed in the entire study population (n=104), with 52(50%) patients reporting oligomenorrhoea. Conclusion: Underlying PCOS is frequent finding in women presenting with acne vulgaris, particularly with associated symptoms like..